2018
DOI: 10.3390/pr6090165
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance on Draw Solutes Development in Forward Osmosis

Abstract: In recent years, membrane technologies have been developed to address water shortage and energy crisis. Forward osmosis (FO), as an emerging membrane-based water treatment technology, employs an extremely concentrated draw solution (DS) to draw water pass through the semi-permeable membrane from a feed solution. DS as a critical material in FO process plays a key role in determining separation performance and energy cost. Most of existing DSs after FO still require a regeneration step making its return to init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 144 publications
0
33
0
Order By: Relevance
“…We were particularly inspired by the successful use of ionic liquids as DS [40][41][42]. Hydrophilic nanoparticles were intensively studied as draw solutes in FO in the recent past due to advantages such as easy separation and regeneration via ultrafiltration (UF), and low generated back-flux during the FO process [43][44][45][46]. The ease of separation opens the route towards the regeneration of the nanoparticles and therefore towards the design of closed osmosis-regeneration processes.…”
Section: Figure 1 Chemical Constitution Of An Ionosilicamentioning
confidence: 99%
“…We were particularly inspired by the successful use of ionic liquids as DS [40][41][42]. Hydrophilic nanoparticles were intensively studied as draw solutes in FO in the recent past due to advantages such as easy separation and regeneration via ultrafiltration (UF), and low generated back-flux during the FO process [43][44][45][46]. The ease of separation opens the route towards the regeneration of the nanoparticles and therefore towards the design of closed osmosis-regeneration processes.…”
Section: Figure 1 Chemical Constitution Of An Ionosilicamentioning
confidence: 99%
“…An ideal draw solution must have the following characteristics: allowing for high water flux, minimal reverse draw solute flux, no toxicity, reasonably low cost, easy and low-cost recovery and compatible with feed purpose (facing the draw salt diffusion risk). Numerous studies reported various draw solutions and draw recovery processes ( Table 6 ; [ 26 , 256 , 257 ]). Draw selection in the context of concentration will involve the specific consideration of the following elements: Osmotic pressure should be in line with the required concentration level and the initial osmotic pressure of the feed solution to be treated.…”
Section: Tuning Fo Process To Tackle Current Limitations For Optimmentioning
confidence: 99%
“…DS regeneration step will consume energy, which renders the necessity to find methods that could reduce energy consumption. Long et al conducted a review analyzing the types of energy applied in DS regeneration [15]. Some DS (e.g., natural sugar, fertilizer) can be directly used without recovery, constituting the most effective way of saving energy.…”
Section: Forward Osmosis (Fo)mentioning
confidence: 99%